2004
DOI: 10.1081/jbc-200045091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 50-Hz Powerline Exposed Magnetized Water on Rat Kidney

Abstract: Double distilled water samples were exposed for 48 hr. to 50 Hz-powerline electromagnetic field (EMF) strength of 51.2 T (36.2 RMS). This EMF exposed water was made available to experimental adult Charles-Foster male rats for drinking ad libitum for 30 days. On the 31st day the rats were anaesthetised with ether and then fixed by perfusion with 10% neutral formalin. The Kidneys were dissected out and further fixed in the same fixative. The corresponding control rats provided with unexposed triple distilled wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Magnetic pre-treatment to water alters its chemistry with respect to pH, ionic composition and microbe mutation which impacts the quality of drinking water in a positive and negative manner [98][99][100]. In one study, double distilled water samples were exposed for 48 h to 50 Hz powerline electromagnetic field (EMF) strength of 51.2 T (36.2 RMS).…”
Section: Direct Purificationmentioning
confidence: 99%
“…Magnetic pre-treatment to water alters its chemistry with respect to pH, ionic composition and microbe mutation which impacts the quality of drinking water in a positive and negative manner [98][99][100]. In one study, double distilled water samples were exposed for 48 h to 50 Hz powerline electromagnetic field (EMF) strength of 51.2 T (36.2 RMS).…”
Section: Direct Purificationmentioning
confidence: 99%
“…The impact of EMF in rats causes decreased hemoglobin oxygen-binding capacity; i.e., hypoxia does not exclude kidney damage contributions. It also has to be supposed that radiation influences hematopoiesis in the blood and bone marrow in the animals ( Singh et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, magnetic field technique can potentially cause some health problems. It was reported that the use of magnetically treated water negatively affects the functionality of rats' kidneys suggesting that magnetic treatment can cause unstable changes to bio-mechanisms of tissue fluid [46]. Generally, electrical, magnetic, and UV treatments require mixing to ensure uniform effective treatments which adds to energy requirements of these techniques.…”
Section: Doc Removal With Physical Methodsmentioning
confidence: 99%